2020
DOI: 10.3389/fonc.2020.00694
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SphK2 Reverses Acquired Resistance of Regorafenib in Hepatocellular Carcinoma

Abstract: Background: Regorafenib is a second-line therapy drug used for advanced hepatocellular carcinoma (HCC). Unfortunately, the survival benefit of the patients receiving this treatment is modest, which may be attributed to drug resistance. In the present study, sphingosine kinase 2 (SphK2) was targeted to reverse regorafenib resistance in HCC. Methods: The functions of SphK2 and sphingosine-1-phosphate (S1P), the catalytic product of SphK2 in regorafenib resistance of HCC cells, were evaluated by cell counting kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Studies have shown that S1P promotes the activation of STAT3 in non-PASMCs ( 20 , 21 ). To examine the effect of S1P on STAT3 in PASMCs, cells were stimulated with 1000-nM S1P at different time points, and Western blotting was performed to detect the phosphorylation level of STAT3 and total STAT3 level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that S1P promotes the activation of STAT3 in non-PASMCs ( 20 , 21 ). To examine the effect of S1P on STAT3 in PASMCs, cells were stimulated with 1000-nM S1P at different time points, and Western blotting was performed to detect the phosphorylation level of STAT3 and total STAT3 level.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs are small noncoding RNAs that bind to the 3' untranslated regions of the target genes, thereby inhibiting translation and/or inducing degradation of target mRNAs. It has been shown that signal transducers and activators of transcription 3 (STAT3), an important downstream of S1P ( 20 , 21 ), mediates the expression of miR-135b in lymphoma cells ( 22 , 23 ). Meanwhile, miR-135b can downregulate the expression of the β-transduction repeat-containing protein (β-TrCP) in lung cancer cells ( 24 ) and hepatocellular carcinoma cells ( 25 ).…”
mentioning
confidence: 99%
“…The decrease in proliferation is mediated by inhibition of SPHK2 activity ( 82 , 85 , 97 ), S1P depletion ( 76 , 79 , 84 , 85 , 95 , 97 , 99 ), accumulation of ceramide ( 79 , 84 , 85 , 89 , 99 ), induction of apoptosis (increased caspase cleavage, decreased Bcl-2 levels, and decreased NOXA transcription) ( 76 , 78 , 79 , 84 91 , 94 96 , 98 , 99 , 102 , 103 ), induction of autophagy (increased LC3-II and beclin-1 levels) ( 77 , 83 , 98 ), estrogen/androgen receptor signaling (decrease in progesterone or androgen receptor levels) ( 75 , 81 , 82 ), cell cycle arrest (increased Myt1, p-cdc2, p53, and p21 levels and decreased pRb, cyclin B1, and cyclin D1 levels) ( 81 , 85 87 , 100 , 101 ), and modulation of cell survival pathways (decrease or inhibition of NF-κB, pERK1/2, pJNK, pAKT, c-Myc, and survivin expression, as well as p21-activated kinase 1 (PAK1)/p-Lin-11/Isl-1/Mec-3 kinase 1 (LIMK1)/Cofilin1 signaling) ( 77 , 78 , 81 , 82 , 84 , 87 , 90 92 , 100 103 ) ( Figure 3 ). The combination of ABC294640 with other drugs, such as regorafenib, sorafenib, PDMP, and ABT-199, induces synergistic potentiation of the treatment effect, reducing chemoresistance in various cancer types ( 98 , 99 , 103 , 104 ). For example, SPHK2/SPP1 arbitrates regorafenib resistance by activating signal transducer and activator of transcription 3 (STAT3) and nuclear factor kappa light chain enhancer of activated B cells (NF-κB).…”
Section: Abc294640mentioning
confidence: 99%
“…Meanwhile, the Hippo and IGF/IGF-1R signaling pathways were demonstrated to be linked in conferring sorafenib resistance in HCC cells [ 163 ]. Additional investigations into mechanisms behind regorafenib resistance in HCC found that resistance is mediated via proteins controlling the cell cycle and proliferation—NF-κB, STAT3, Akt, cMyc [ 252 , 253 , 254 , 255 ]. Thus, the IGF/IGF-1R signaling may be a potential target for combination treatment with regorafenib.…”
Section: Igf/igf-1r Signaling Responses For Targeted-drugs Resistamentioning
confidence: 99%